Role of Foreign Direct Investment in Retail Sector in Indian Perspective - Kumar, Santosh (Journal of Commerce and Trade, 2012)
The Concept of Foreign Direct Investment is now a part of India’s economic future but the term remains vague to many, despite the profound effects on the economy. FDI is allowed up to 51% investment in single brand retail but government is going to open the doors for Multi Brand investment. India is the second most attractive retail destination, globally from among thirty emergent markets so foreign investors are curious to invest in India in so many sectors. It has made India the cynosure of many foreign eyes. FDI in multi brand can effect our economy by so many ways. This paper shows the different dimensions of FDI in multi brand retailing. The Indian media regularly discusses the issues of FDI in Retailing.